Chronic low dose 90Sr contamination in Lemna minor: from transcriptional dynamics of epigenetic regulators to population level effects - Boldrini, Luca; Van Hees, May; Duarte, Gustavo Turqueto; Nauts, Robin; Wannijn, Jean; Reymen, Yelltrich; De Rouck, Brix; Loots, Hilde; Schiavinato, Matteo; Selck, Henriette; Horemans, Nele (Frontiers in Plant Science, 2025)
The ecotoxicology model plant Lemna minor was exposed for 6 weeks to 90Sr, simulating the dose rates present in the Chernobyl Exclusion Zone (CEZ), in order to understand the effects of chronic low dose ionising radiation exposure. The data suggest that the plant may exhibit temporally variable acclimation responses that can be interpreted as early-, mid-, and long-term phases. Morphological changes included increased area and frond number, while molecular adjustments encompassed variations in pigment levels, glutathione metabolism, and expression modulation of telomerase-related and DNA methylation machinery genes. Physiological parameters and 90Sr uptake remained relatively stable, yet fluctuations indicate a continuous adjustment to the chronic stress, suggesting L. minor’s potential for phytoremediation. The interplay between transcriptional regulation of DNA methylation and the examined endpoints suggests a potential involvement of epigenetic mechanisms in L. minor’s acclimation to chronic low dose-rate 90Sr stress. This work provides knowledge on L. minor’s abiotic stress responses and contributes to our understanding of plant adaptation to low-level ionising radiation (IR). The findings contribute to the development of adverse outcome pathways (AOPs) for L. minor exposed to IR, improving environmental risk assessment approaches.